The Impacts of Innovative Institutions in Higher Education - Coburn, Noah.; Derby-Talbot, Ryan. (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
As they have done historically, innovative institutions enrich the college ecosystem, helping the higher educational industry develop flexible resilience. The chapters in this book showcase perspectives, hard-won lessons, challenges and provocative ideas about how historically innovative institutions can contribute to the current discourse on innovation in higher education. The chapters in this book include case studies of innovative campuses and practices, as well as future-looking directions for innovation. Taken together, they ask, is there a way to consider how future trends can be navigated in effective ways, so that the most important features of higher education--student learning, the liberal arts, the cultivation of critical thinking--can remain central to tomorrow's institutions?
Introduction: How Innovative Institutions Enrich Higher Education -- Webs of Connection and Moments of Friction: Dynamics of Ownership and Relationship Between Students and Faculty at a Small Innovative College -- After Eden: The Civic and Social Potential of Innovative Higher Education -- Empowering Students Through Evaluation: Over 50 Years Without Grades at Hampshire College -- Innovating as an Embedded Program at a Larger State University: New College in Three Pivotal Moments -- El Colegio Chicano Del Pueblo: Decolonizing Chicano Education and the Search for Self-Determination -- Agility or Stability: Can a School Have Both in Faculty Hiring? -- Innovative Scheduling: The Intensive Delivery of Higher Education -- The Role of Mentoring in Innovative Progressive Institutions -- When Innovative Universities Fail: Quest University, Partnerships, Financial Sustainability -- Assessment, Outcomes, and Innovation in Higher Education -- Beyond "Innovation": Lessons for Making Change in Higher Educational Institutions.
Keywords: Education, Higher; Teaching; Education and state; Higher Education; Pedagogy; Educational Policy and Politics